Production Plan To Minimize Production Cost In Cv Una Surya Putra Mandiri - Prakasa, Syahidan Fauzan; Damayanti , Dida Diah; Nopendri, Nopendri (eProceedings of Engineering, 2024)
Indonesia as the world's archipelagic country haveIndonesia have almost 3,8 million hectares of coconut plant. Thatlead Indonesia to one of the biggest countries in exporting thecoconut product. One of the products that has been exported isdesiccated coconut. The interest of desiccated coconut isincreasing in several countries. CV Una Surya Putra Mandiri isone of the that producing the desiccated coconut. This companyuse the principle of make to stock because of the raw material thatwas easy to be spoiled. Due to the uncertainty of the demandfluctuations, the company was struggling in producing the rightyamount of product. So, the production of the company mostly getoverproduction that cause the overstock in inventory while theproduction must go on. Based on the problem occur, this researchhas an objective to minimize the overproduction and backorder. Inminimized the production cost, they are needing a productionplanning. In the other word, production planning will bedetermined the forecasting demand, the resource availability, andthe schedule to fulfil the demand. The output in this research isfinding the minimum production cost using the plannedproduction to fulfil the demand Keywords: Production Planning, Demand Forecasting, RoughCut Capacity Planning, Scheduling, Uncontrolled Production